Prevalence of peripheral neuropathy in newly diagnosed type 2 diabetics in sub-district hospital Bishnah - Chander, Kalash (International Journal of Advances in Medicine, 2021)
Background: Diabetic neuropathy is a loss of sensory function beginning distally in the lower extremities that is also characterized by pain and substantial morbidity. Screening and early identification of neuropathy among diabetics can be a crucial opportunity for course modulation for keeping the glycemic control to optimal levels and within recommended targets. Methods: A cross sectional observational study were conducted on 100 patients older than 30 years, of newly diagnosed type 2 diabetes mellitus (T2DM) and attending medicine OPD of sub district hospital Bishnah, district Jammu, Jammu and Kashmir from April 2020 to January 2021. Diabetic peripheral neuropathy (DPN) was diagnosed if two or more of the abnormalities of neuropathy symptoms score or neuropathy disability score were present. Results: Among the studied subjects, 59% were males and 41% were females. Mean age was 49.22±10.63 years for diabetics. 29% patients were alcoholic and 24% were smokers and body mass index (BMI) of more than 25 was found in 20% of patients. Most common of symptoms was tingling (37.14%). 29 subjects had neuropathic signs and neuropathy disability score (NDS) more than or equal to 2 with 28 of them having reduced nerve conduction velocity and loss of vibration in 65.52% patients. A higher prevalence of DPN was found among DM duration of greater than 5 years. Conclusions: The present study showed a significant correlation between DPN, duration of diabetes and BMI. Detection of neuropathic symptoms and complications is therefore essential among patients with T2DM before it hampers their quality of life.